Explaining the scatter in the galaxy mass–metallicity relation with gas flows. Issue 4 (4th May 2021) - van Loon, Maria L; Mitchell, Peter D; Schaye, Joop
ABSTRACT: The physical origin of the scatter in the relation between galaxy stellar mass and the metallicity of the interstellar medium, i.e. the mass–metallicity relation (MZR), reflects the relative importance of key processes in galaxy evolution. The eagle cosmological hydrodynamical simulation is used to investigate the correlations between the residuals of the MZR and the residuals of the relations between stellar mass and, respectively, specific inflow, outflow, and star formation rate as well as the gas fraction for central galaxies. At low redshift, all these residuals are found to be anticorrelated with the residuals of the MZR for M ⋆ /M⊙ ≲ 10 10 . The correlations between the residuals of the MZR and the residuals of the other relations with mass are interrelated, but we find that gas fraction, specific inflow rate, and specific outflow rate all have at least some independent influence on the scatter of the MZR. We find that, while for M ⋆ /M⊙ > 10 10.4 the specific mass of the nuclear black hole is most important, for M ⋆ /M⊙ ≲ 10 10.3 gas fraction and specific inflow rate are the variables that correlate most strongly with the MZR scatter. The time-scales involved in the residual correlations and the time that galaxies stay above the MZR are revealed to be a few Gyr. However, most galaxies that are below the MZR at z  = 0 have been below the MZR throughout their lifetimes.